Peningkatan Kemampuan Pemecahan Masalah Matematis dan Keaktifan Belajar Siswa Melalui Model Pembelajaran LAPS-Heuristik - Nita Rahayu; Karso Karso; Sendi Ramdhani (IndoMath: Indonesia Mathematics Education, 2019)
The purpose of the research to find out whether the increase in mathematical problem solving abilities of students using the LAPS-Heuristic learning model is better than the mathematical problem solving abilities of students who use conventional learning models, how students' learning activeness attitudes towards mathematics learning using the LAPS-Heuristic learning model, and obstacles in completing problems solving. The research method used was a quasi-experimental research design with Nonequivalent control group design. The experimental class obtained learning with the LAPS-Heuristic learning model and the control class with conventional learning models. The participant in this research is all of students at seven grade. The samples used were two classes from eleven classes selected by purposive sampling technique. To obtain data from the research results, a problem solving ability test instrument was used, a questionnaire on student learning activeness, and an interview. Based on the results of data analysis the improvement of students 'mathematical problem solving abilities using the LAPS-Heuristic learning model is better than students who use conventional learning models, the students' learning activeness in the LAPS-Heuristic learning model is almost entirely positive. The obstacles experienced by students in solving the problems of mathematical problem solving abilities are that students find it difficult to understand question the problem solving abilities so that it is difficult to develop a plan to solve problems that cause obstacles in counting operations that require accuracy.